BETON RINGAN : PEMBUATAN TIMBER CREATE BERBAHAN SELOLUSA YANG RAMAH LINGKUNGAN - Amiruddin Amiruddin; Sukarman Sukarman (PILAR, 2015)
In the construction world, concrete is a material that is widely used and is a major component of the building. Excess concrete, among others, has a higher compressive strength than tensile strength, easy to set up, requires no special care, easy stacking of materials obtained from the enviorment, and is more durable than other building materials. However, concrete has a shortage of great weight of the contents so that the load capacity to be sustained relatively larger foundation.The produce bulk density lighter concrete with compressive strenght is relatively larger in order to ease the burned of the foundation, it would require replacement of one of the concrete composition in order to get a lighter weigth. Sawdust, is one of the materials selected as a substitute for fine aggregate (sand), to obtain a lighter weight concrete. Sawdust used are acacia, with the percentage taken proportional to the weight of the cement, but the number does not change but the percentage of cement is replaced heavy fine aggregate (sand).From the tests performed by the replacement of the composition, obtained a large percentage of the limit to get the concrete compressive strength 175 kg/cm2 is 4% with a reduction in the compressive strength of 40.527% of the normal concrete with compressive strength value is 184.444 kg/cm2 and bulk density values were also concrete decreased by 11.128% of the weight of concrete the normal value to 2011.704 kg/m3. For the lightweight concrete obtained look at the composition of the addition of 100% sawdust and 50% of the cement composition beginning with the compressive strength of concrete produces 72.222 kg/cm2 and the weight content of the concrete values is 1243.259 kg/m3 which is the result meets the quality standards of lightweight concrete according to the Procedure for Making Mixed Concrete plan light, 2002, that the value of the compressive strength of 70.234 kg/cm2 – 175.331 kg/cm2 and a weight of lightweight concrete content of 800 kg/m3 – 1400 kg/m3.